Hungarian Monitoring, 29 March 1990 . [Magyar rádiófigyelő], 1990. március 29 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - The Lithuanian question; Swedish position on the situation in Lithuania - USSR wants Poland to repay its ruble debt in USD - Opening talks on forming coalition government held in GDR Domestic Affairs: - Parliament: draft law on general amnesty, retroactive interest taxation abolished, committee overseeing radio and TV abolished - Alliance of Free Democrats (SZDSZ) and Alliance of Young Democrats (Fidesz) support each other in second round with joint withdrawals - József Antall gives interview to Die Welt - Alliance of Young Democrats (Fidesz) sympathy protests for Lithuania - Romanian-Hungarian tensions Economy: - Hungarian Socialist Workers' Party (MSZMP) property scandal Külpolitika: - A litván kérdés; svéd állásfoglalás a litván helyzettel kapcsolatban - A SZU azt akarja, hogy Lengyelország dollárban fizesse ki rubel tartozását - Az NDK-ban megtartották a nyitó tárgyalást a kormánykoalíció kialakítására Belpolitika: - Országgyűlés: közkegyelemről szóló törvényjavaslat, kamatadó visszamenőleges megszüntetése, megszűnt a rádiót és TV-t felügyelő kuratórium - Az SZDSZ és a FIDESZ kölcsönös visszalépésekkel támogatják egymást a második fordulón - Antall József interjú a Die Weltnek - FIDESZ rokonszenvtüntetés Litvánia mellett - Román-magyar feszültségek Gazdaság: - MSZMP vagyon körüli botrány